Studi Literature Penggunaan Media Pembelajaran Menggunakan Teknologi Augmented Reality Pada Sekolah Kejuruan - Pratama, Arief Juneirul; Irfan, Dedy; Effendi, Hansi (Universitas Negeri Padang, 2023)
The challenges Indonesia had throughout the Industry 4.0 led to an improvement in the quality of its human resources, which was followed by the standard of its current education. To positively impact the growth of the nation, education must be able to provide quality human resources. One of the educational institutions that tries to give students the competency skills they need to succeed in the workplace (DUDI) is the vocational school . The advancement of information technology offers creative learning media alternatives. Technology-based multimedia such as augmented reality can be applied as a teaching tool. The application of augmented reality in the classroom can enhance its fun, interactivity, and accessibility. By gathering information sources linked to the issues highlighted in a study, a literature review methodology will be used as the research method. Using Augmented Reality (AR) technology, learning media has an average validity score of 86.54% with a very valid category, according to the results of the research that has been done, while the average effectiveness score is 84.96% with a very effective category. Learning indicators with learning objectives, learning media that are in line with core competencies and fundamental competencies, as well as needs and advantages of students, are used to gauge the validity of learning materials. In the meanwhile, student response, student activities, learning outcomes, and learning management are used to gauge the effectiveness of learning media.